New benchmarks to design clinical trials with advanced or metastatic liposarcoma or synovial sarcoma patients: An EORTC – Soft Tissue and Bone Sarcoma Group (STBSG) meta-analysis based on a literature review for soft-tissue sarcomas. (October 2022) - Kantidakis, Georgios; Litière, Saskia; Neven, Anouk; Vinches, Marie; Judson, Ian; Blay, Jean-Yves; Wardelmann, Eva; Stacchiotti, Silvia; D'Ambrosio, Lorenzo; Marréaud, Sandrine; van der Graaf, Winette T.A.; Kasper, Bernd; et al.
Abstract: Background: Recently, we performed a meta-analysis based on a literature review for STS trials (published 2003–2018, ≥10 adult patients) to update long-standing reference values for leiomyosarcomas. This work is extended for liposarcomas (LPS) and synovial sarcomas (SS). Materials and methods: Study endpoints were progression-free survival rates (PFSRs) at 3 and 6 months. Trial-specific estimates were pooled per treatment line (first-line or pre-treated) with random effects meta-analyses. The choice of the therapeutic benefit to target in future trials was guided by the European Society for Medical Oncology Magnitude of Clinical Benefit Scale (ESMO-MCBS). Results: Information was acquired for 1030 LPS patients (25 trials; 7 first-line, 17 pre-treated, 1 both) and 348 SS patients (13 trials; 3 first-line, 10 pre-treated). For LPS, the overall pooled first-line PFSRs were 69% (95%-CI 60–77%) and 56% (95%-CI 45–67%) at 3 and 6 months, respectively. These rates were 49% (95%-CI 40–57%)/28% (95%-CI 22–34%) for >1 lines. For SS, first-line PFSRs were 74% (95%-CI 58–86%)/56% (95%-CI 31–78%) at 3 and 6 months, and pre-treated rates were 45% (95%-CI 34–57%)/25% (95%-CI 16–36%). Following ESMO-MCBS guidelines, the minimum values to target are 79% and 69% for first-line LPS (82% and 69% for SS) at 3 and 6 months. For pre-treated LPS, recommended PFSRs at 3 and 6 months suggesting drug activity are 63% and 44% (60% and 41% for SS). Conclusions: New benchmarks are proposed for advanced/metastatic LPS or SS to design future histology-specific phase II trials. More data are needed to provide definitive thresholds for the different LPS subtypes. Highlights: Update and recalibrate long-standing reference values for soft-tissue sarcomas. Extension of previous novel meta-analysis for advanced/metastatic leiomyosarcoma. Information acquired for 1030 liposarcoma and 348 synovial sarcoma patients. Minimum values to target as per ESMO Magnitude of Clinical Benefit Scale. Need to raise the bar in the design of future histology-tailored phase II trials.